Pengaruh Mekanisme Corporate Governance, Ukuran KAP, Audit Tenure Dan Audit Report Lag Pada Integritas Laporan Keuangan - Amrulloh, Amrulloh; Asri Dwija Putri, IG.A. Made; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.08. TAHUN 2016, 2016)
A public company listed at Indonesia Stock Exchange (BEI) is required to comply the regulations that have been set by the Financial Services Authority (OJK), one of the regulation are financial statements audited by an independent auditor. An Integrity financial report must meet several requirements such as relevant, reliable, accurate and shows the actual performance of the company. Financial manipulation that occurred in Indonesia in recent years have showed symptoms of a failure in the integrity of financial statements, Financial statement is no longer show the actual condition of the company's performance. This study aims to discuss the influence of corporate governance mechanisms (Institutional Ownership, Managerial Ownership, Audit Committee, Independent Commissioner), Firm Size, Audit Tenure and Audit Report Lag to Financial Integrity report (empirical studies on financial sector companies listed at the Stock Exchange the period 2011- 2013)
Keywords: Good Corporate Governance, Institutional Ownership; Managerial Ownership, Independent Commissioner; Audit Committee; Firm Size; Audit Tenure and Audit Report Lag and integrity of financial statements.